Peran Psikologi Sosial dalam Kampanye Sosial Literasi Kekerasan Berbasis Gender Online untuk Melindungi Self-Image pada Gen Z di Forum Anak Kota Bekasi (FORAKSI) - Murtanti Putri, Dianingtyas; Hanathasia, Mirana; Kania, Dessy; Fortunisa, Ananda (LPkM Universitas Bakrie, 2022)
Online gender-basis violence (KBGO) is violence through digital technology aimed at someone based on their gender or gender identity. This violence is not carried out physically, but through online harassment through social media which is used by manipulating information, including illegal content, and so on, one which aims to damage the reputation or credibility of the victim, which can cause psychological harm, social isolation, and economy harm. Meanwhile, the participants who will take part in this training activity are Generation Z, then the problem to be overcome is to provide a briefing to Generation Z regarding the misuse of social media use which can have an impact on their self-image and personal branding, therefore it is important to be given an understanding of digital content strategies, especially social media. In addition, it is hoped that by getting this activity they will raise awareness to protect their data so that they become agents of change to their peers. The method used in this Community Service (PkM) activity will be carried out into three stages, namely the preparation stage, the implementation stage, and the evaluation stage. Furthermore, the activities that will be carried out are providing assistance and training to partners of the Bekasi City Children's Forum (FORAKSI).